Polyaniline and manganese oxide decorated on carbon nanofibers as a superior electrode material for supercapacitor - Jalil, Nurul Ain; Mohd Abdah, Muhammad Amirul Aizat; Azman, Nur Hawa Nabilah; Sulaiman, Yusran (Elsevier, 2020)
A novel ternary composite of carbon nanofibers/polyaniline‑manganese oxide (CNFs/PANI-MnO2) was synthesized via electrospinning, carbonization followed by electrodeposition of PANI-MnO2. The CNFs/PANI-MnO2 composite exhibited excellent specific capacitance of 937.66 F/g at a scan rate of 5 mV/s and good cyclic stability with capacitance retention of 97.6% after 5000 consecutive cycles. The composite also exhibited superior performance with a specific energy of 66.12 Wh/kg at a specific power of 470.81 W/kg with low charge transfer resistance, Rct (1.81 Ω) and equivalent series resistance (32.18 Ω) indicating high electronic conductivity. Three symmetrical CNFs/PANI-MnO2 composites assembled in series using coin cells have successfully lighted up a red-light emitting diode (LED), proving its outstanding supercapacitive performance as an excellent electrode material for supercapacitors.